Core outcome sets in dermatology: report from the second meeting of the International Cochrane Skin Group Core Outcome Set Initiative. (14th February 2018) - Kottner, J.; Jacobi, L.; Hahnel, E.; Alam, M.; Balzer, K.; Beeckman, D.; Busard, C.; Chalmers, J.; Deckert, S.; Eleftheriadou, V.; Furlan, K.; Horbach, S.E.R.; et al.
Summary: Results of clinical trials are the most important information source for generating external clinical evidence. The use of different outcomes across trials, which investigate similar interventions for similar patient groups, significantly limits the interpretation, comparability and clinical application of trial results. Core outcome sets (COSs) aim to overcome this limitation. A COS is an agreed standardized collection of outcomes that should be measured and reported in all clinical trials for a specific clinical condition. The Core Outcome Set Initiative within the Cochrane Skin Group (CSG‐COUSIN) supports the development of core outcomes in dermatology. In the second CSG‐COUSIN meeting held in 2017, 11 COS development groups working on skin diseases presented their current work. The presentations and discussions identified the following overarching methodological challenges for COS development in dermatology: it is not always easy to define the disease focus of a COS; the optimal method for outcome domain identification and level of detail needed to specify such domains is challenging to many; decision rules within Delphi surveys need to be improved; appropriate ways of patient involvement are not always clear. In addition, there appear to be outcome domains that may be relevant as potential core outcome domains for the majority of skin diseases. The close collaboration between methodologists in the Core Outcome Set Initiative and the international Cochrane Skin Group has major advantages for trialists, systematic reviewers and COS developers. Abstract : What's already known about this topic? Far too many outcomes are used in dermatological clinical trials that hamper meaningful comparisons that in turn affects care for patients. Core outcome sets (COSs) are an agreed standardized collection of outcomes that should be included in all clinical trials for a specific health condition. The Core Outcome Set Initiative within the Cochrane Skin Group (CSG‐COUSIN) was established to support the development of COSs in dermatology. What does this study add? The second meeting of CSG‐COUSIN took place in 2017 and included updates from 11 core outcome projects. Research gaps identified included the need to develop more guidance on how to appropriately define the focus of a COS, how to identify the core domains, how to best involve patients and which are the most useful decision rules within Delphi surveys when developing COSs. The meeting concluded that some common outcome domains may be applicable to dermatological diseases in general. Linked Article: Apfelbacher Br J Dermatol 2018; 178 :837–838 Plain language summary available online